ANTIBACTERIAL ACTIVITIES OF SAPODILLA FRUIT EXTRACT INHIBITING SALMONELLA TYPHI ON MICE BALB/c - IDRUS, HASTA HANDAYANI; HATTA, MOCHMAMMAD; FEBRIZA, AMI; KASIM, VIVIEN NOVARINA A. (International Journal of Applied Pharmaceutics, 2019)
Objective: The aim of this study was to see the effectiveness of brown manila extract in inhibiting the growth of Salmonella typhi Thy1 bacteria in peritoneal fluid male mice strain BALB/c. Methods: We use manila extract which has been obtained from the extraction of the maceration method and uses the plate count agar (PCA) method to calculate the number of colonies after conducting bacterial culture before and after the intervention. Results: The results obtained were a significant decrease of bacterial colonies after administration of manila extract 510 mg/kgBW value p=0.009 and extract of brown manila 750 mg/kgBB value p=0.007. Conclusion: Giving extract of mano manila 510 mg/kgBB and 750 mg/kgBB has effectiveness in suppressing the growth of S. typhi Thy1.